Revitalisasi Sekolah Berbasis Budaya Mutu - Hendro Widodo (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2018)
In the context of education, quality includes inputs, processes, and outputs. The three elements are interconnected. That is, to produce a quality educational output, influenced by the process of education, and quality education process will be able to produce better output if supported by the input of quality education as well. Schools can be said to be of quality if the inputs, processes, and output of education can meet the requirements demanded by users of education services, both internal and external. In this case, school quality management is the ability of schools to utilize educational resources both human and non-human resources to improve the ability of inputs, processes, and outputs of education to meet the requirements demanded by users of education services (stakeholders). Keywords: Revitalization, Schooling, and Quality Culture. AbstrakDalam konteks pendidikan, mutu mencakup input, proses, dan output. Ketiga unsur tersebut saling berhubungan. Artinya, untuk menghasilkan output pendidikan yang bermutu, dipengaruhi oleh proses pendidikannya, dan proses pendidikan yang bermutu akan dapat menghasilkan output yang lebih bermutu bilamana didukung oleh input pendidikan yang bermutu pula. Sekolah dapat dikatakan bermutu jika input, proses dan output pendidikannya dapat memenuhi persyaratan yang dituntut oleh pengguna jasa pendidikan, baik internal maupun eksternal. Dalam hal ini, manajemen mutu sekolah merupakan kemampuan sekolah dalam mendayagunakan sumber daya pendidikan baik sumber daya manusia maupun non manusia untuk meningkatkan kemampuan input, proses dan output pendidikan guna memenuhi persyaratan yang dituntut oleh pengguna jasa pendidikan (stakeholders).  Kata Kunci: Revitalisasi, Sekolah, dan Budaya Mutu.